2021
DOI: 10.1016/j.celrep.2021.108801
|View full text |Cite
|
Sign up to set email alerts
|

Two septal-entorhinal GABAergic projections differentially control coding properties of spatially tuned neurons in the medial entorhinal cortex

Abstract: Septal parvalbumin-expressing (PV + ) and calbindin-expressing (CB + ) projections inhibit low-threshold and fast-spiking interneurons, respectively, in the medial entorhinal cortex (MEC). We investigate how the two inputs control neuronal activity in the MEC in freely moving mice. Stimulation of PV + and CB + terminals causes disinhibition of spatially tuned MEC neurons, but exerts differential effects on temporal coding and burst firing. Thus, recruitment of PV + projections disrupts theta-rhythmic firing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…In particular whether a role in motivated behaviour and place preference was specific to BA input, or due to the dorso-ventral location of this input in hippocampus. Interestingly, long range inhibition from entorhinal cortex, septum and PFC all preferentially target interneurons and avoid pyramidal neurons (Basu et al, 2016;Malik et al, 2021;Melzer et al, 2012;Schlesiger et al, 2021). In contrast our data shows that BA long range inhibition connects with both interneurons and pyramidal neurons (Figure 3), similar to that seen in long range inhibitory projections from BA to PFC (Seo et al, 2016).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In particular whether a role in motivated behaviour and place preference was specific to BA input, or due to the dorso-ventral location of this input in hippocampus. Interestingly, long range inhibition from entorhinal cortex, septum and PFC all preferentially target interneurons and avoid pyramidal neurons (Basu et al, 2016;Malik et al, 2021;Melzer et al, 2012;Schlesiger et al, 2021). In contrast our data shows that BA long range inhibition connects with both interneurons and pyramidal neurons (Figure 3), similar to that seen in long range inhibitory projections from BA to PFC (Seo et al, 2016).…”
Section: Discussionsupporting
confidence: 55%
“…For example, functional inhibitory projections from PFC to NAc (A. T. Lee et al, 2014), and BA to PFC (Seo et al, 2016) have both been shown to modulate value-based and reward behaviour, including the support of real time place preference and aversion. The hippocampus also receives long range inhibitory input from numerous regions including entorhinal cortex (Basu et al, 2016; Melzer et al, 2012), septum (Schlesiger et al, 2021) and PFC (Malik et al, 2021). While these studies focussed on dorsal hippocampal circuitry and a role for these projections in memory and navigation, due to the known dichotomy between dorsal and ventral hippocampal function (Fanselow and Dong, 2010; Strange et al, 2014), it would be interesting to investigate the presence and function of such long range inhibitory projections into vH.…”
Section: Discussionmentioning
confidence: 99%
“…In particular whether a role in motivated behaviour and place preference was specific to BA input, or due to the dorso-ventral location of this input in hippocampus. Interestingly, long range inhibition from entorhinal cortex, septum and PFC all preferentially target interneurons and avoid pyramidal neurons (Basu et al, 2016;Melzer et al, 2012;Schlesiger et al, 2021). In contrast our data shows that BA long range inhibition connects with both interneurons and pyramidal neurons (Figure 4), similar to that seen in long range inhibitory projections from BA to PFC (Seo et al, 2016).…”
Section: Discussionsupporting
confidence: 54%
“…For example, functional inhibitory projections from PFC to NAc (A. T. , and BA to PFC (Seo et al, 2016) have both been shown to modulate value-based and reward behaviour, including the support of real time place preference and aversion. The hippocampus also receives long range inhibitory input from numerous regions including entorhinal (Basu et al, 2016;Melzer et al, 2012), septum (Schlesiger et al, 2021) and PFC (Malik et al, 2021). While these studies focussed on dorsal hippocampal circuitry and a role for these projections in memory and navigation, due to the known dichotomy between dorsal and ventral hippocampal function (Fanselow and Dong, 2010;Strange et al, 2014), it would be interesting to investigate the presence and function of such long-range inhibitory projections into vH.…”
Section: Discussionmentioning
confidence: 99%
“…They may play a role in guiding an animal's action based on its internal state, thus modifying locomotor responses based on possible threatening stimuli present in the environment (Mikulovic et al, 2018). GABAergic septal interneurons, on the other side, are highly interconnected inside the MSDB and with the HPC formation (Freund and Antal, 1988;Gonzalez-Sulser et al, 2014;Salib et al, 2019;Schlesiger et al, 2021), for this reason they play a major role in pace making activity and theta generation. To our knowledge, they do not send dense projections to other cortical or subcortical regions apart from the HPC formation and some related structures like the retrosplenial cortex (Unal et al, 2015) and their role in behaviour has not been deeply investigated so far.…”
Section: Cell Type Specific Manipulations Of the Msdbmentioning
confidence: 99%